Hubungan Pengetahuan, Sikap, dan Perilaku Gizi Seimbang dengan Tingkat Kebugaran pada Atlet Non-Elit Kategori Stop and Go Sport di UKM Olahraga UNESA: The Relationship Between Knowledge, Attitudes, and Behavior of Balanced Nutrition with Fitness Levels in Non-Elite Athletes of Stop and Go Sport Categories in Sports UKM UNESA - Aiko Aristawati Nabila; Satwika Arya Pratama; Cleonara Yanuar Dini; Rita Ismawati; Endang Sri Wahjuni (UNIVERSITAS NGUDI WALUYO, 2024)
Physical fitness is the physical ability of a person to carry out daily activities without feeling excessive fatigue. In achieving good physical fitness, a proper diet is needed, especially for athletes. Proper dietary habits can be formed through the existence of knowledge, attitudes, and behavior of balanced nutrition that is also appropriate in an athlete. This study aims to determine the relationship between knowledge, attitudes, and behavior of balanced nutrition with the fitness level of non-elite athletes in football, basketball, and volleyball UKM UNESA. This type of research is quantitative with a cross-sectional approach. Respondents in this study amounted to 56 athletes consisting of soccer, basketball, and volleyball athletes obtained by purposive sampling technique. The results of this study indicate the majority of the level of knowledge of balanced nutrition is moderate (59%), the attitude of balanced nutrition is positive (52%), the behavior of balanced nutrition is positive (52%), and physical fitness is less (64%). The results of the study using the Rank Spearman statistical test showed that there was no relationship between knowledge (p value = 0.526 > 0.05) and balanced nutrition attitudes (p value = 0.458 > 0.05) with athletes' physical fitness. While there is a relationship between balanced nutrition behavior and athletes' physical fitness (p value = 0.043 <0.05). Therefore, it can be concluded that there is no relationship between knowledge and attitude of balanced nutrition with physical fitness. But there is a relationship between balanced nutrition behavior and physical fitness. ABSTRAK Kebugaran jasmani merupakan kemampuan fisik seseorang untuk melakukan aktivitas sehari-hari tanpa merasakan kelelahan yang berlebih. Dalam mencapai kebugaran jasmani yang baik diperlukannya pola makan yang tepat terutama bagi atlet. Pembiasaan pola makan yang tepat dapat terbentuk melalui adanya pengetahuan, sikap, dan perilaku gizi seimbang yang tepat pula pada diri seorang atlet. Penelitian ini bertujuan untuk mengetahui hubungan pengetahuan, sikap, dan perilaku gizi seimbang dengan tingkat kebugaran atlet non-elit di UKM sepak bola, basket, dan voli UNESA. Jenis penelitian ini adalah kuantitatif dengan pendekatan secara cross-sectional. Responden pada penelitian ini berjumlah 56 orang atlet yang terdiri dari atlet sepak bola, basket, dan voli yang diperoleh dengan teknik purposive sampling. Hasil penelitian ini menunjukkan mayoritas tingkat pengetahuan gizi seimbang sedang (59%), sikap gizi seimbang positif (52%), perilaku gizi seimbang positif (52%), dan kebugaran jasmani kurang (64%). Hasil penelitian menggunakan uji statistik rank spearman menunjukkan bahwa tidak terdapat hubungan antara pengetahuan (p value = 0,526 > 0,05) dan sikap gizi seimbang (p value = 0,458 > 0,05) dengan kebugaran jasmani atlet. Sedangkan terdapat hubungan antara perilaku gizi seimbang dengan kebugaran jasmani atlet (p value = 0,043 < 0,05). Dengan demikian dapat disimpulkan bahwa tidak terdapat hubungan antara pengetahuan dan sikap gizi seimbang dengan kebugaran jasmani. Akan tetapi, terdapat hubungan antara perilaku gizi seimbang dengan kebugaran jasmani.